Refinements for Bragg coherent X‐ray diffraction imaging: electron backscatter diffraction alignment and strain field computation. Issue 5 (6th September 2022) - Yang, David; Lapington, Mark T.; He, Guanze; Song, Kay; Zhang, Minyi; Barker, Clara; Harder, Ross J.; Cha, Wonsuk; Liu, Wenjun; Phillips, Nicholas W.; Hofmann, Felix
Abstract : A novel and accurate method to align crystalline samples for Bragg coherent X‐ray diffraction imaging using electron backscatter diffraction is presented. An efficient approach using the complex exponential of the phase to calculate the strain is also implemented, for greater accuracy in resolving crystal defects. Abstract : Bragg coherent X‐ray diffraction imaging (BCDI) allows the 3D measurement of lattice strain along the scattering vector for specific microcrystals. If at least three linearly independent reflections are measured, the 3D variation of the full lattice strain tensor within the microcrystal can be recovered. However, this requires knowledge of the crystal orientation, which is typically attained via estimates based on crystal geometry or synchrotron microbeam Laue diffraction measurements. Presented here is an alternative method to determine the crystal orientation for BCDI measurements using electron backscatter diffraction (EBSD) to align Fe–Ni and Co–Fe alloy microcrystals on three different substrates. The orientation matrix is calculated from EBSD Euler angles and compared with the orientation determined using microbeam Laue diffraction. The average angular mismatch between the orientation matrices is less than ∼6°, which is reasonable for the search for Bragg reflections. The use of an orientation matrix derived from EBSD is demonstrated to align and measure five reflections for a single Fe–Ni microcrystal via multi‐reflection BCDI. Using this data set, a refined strain field computation based on the gradient of the complex exponential of the phase is developed. This approach is shown to increase accuracy, especially in the presence of dislocations. The results demonstrate the feasibility of using EBSD to pre‐align BCDI samples and the application of more efficient approaches to determine the full lattice strain tensor with greater accuracy.